Building Self-Awareness as a Creation, Servant, and Caliph Entrusted with Divine Trust - Prakoso, Bayu Teguh; Muhamad Jaffar Bin Taib (Journal of Sufism and Psychotherapy, 2025)
Self-awareness as a creation, servant, and caliph is a fundamental aspect in shaping human character and spirituality as bearers of divine trust. This study aims to examine in depth how this self-awareness is formed and functions within the context of religious and social life. The research method used is qualitative with a case study approach, through in-depth interviews, participatory observation, and document analysis. The results reveal that self-awareness as a creation teaches human limitations and dependence on God, as a servant emphasizes the importance of obedience and devotion, and as a caliph motivates moral and social responsibility in managing the trust of the world. The implications of this study highlight the need to integrate these three aspects of awareness in religious education and guidance to develop complete and responsible individuals. This research provides a unique contribution by combining theological and practical perspectives in building both spiritual and social awareness. These findings can serve as an important reference for developing religious education curricula and character-building strategies in various religious institutions.